INTERTEXTEMES SOURCES OF THE UKRAINIAN INTERNET SEGMENT - Mariana Lavriv (Scientific Journal of Polonia University, 2023)
This work aims to analyze the intertextemes sources of the Ukrainian segment of the Internet. The article examines approaches to the concepts of citation thesaurus and intertextual thesaurus. The functioning of intertextemes of biblical and folklore origin, units that go back to artistic texts of different periods, journalism, advertising, and spoken discourse in Internet texts is studied. During the formation of the factual base of the research, the method of entire selection from texts posted on the Internet was applied. The origin of the units was analyzed, as well as the relevant phraseographic sources, collections of aphorisms, etc. The elements of etymological analysis turned out to be valuable for the analysis of the national and cultural specificity of the intertextual thesaurus. English- and Russian-speaking cultures were significant factors changing the composition of the Ukrainian intertextual thesaurus, particularly in the pre-war period. It has been observed that quotations originating from German, Polish, and French linguistic cultures occur much less often. Given the informality of Internet communication, speakers often attribute the authorship of an expression to a certain person. The work analyzes and singles out some intertextemes- «bastard».